Solution of Kinematic Wave Model Using DQM and Sütçüler Flood Example - Kaya, B.; Keskin, A. (My University, 2012)
Floods are characterized by large discharges, high flow velocities and high water levels. These flood characteristics should be known for all structures to be built in river basins. In this study, Muskingum Method and Kinematic wave model (KWM) are used for flood hydrograph prediction. In the numerical solution of the KWM, the Differential Quadrature Method (DQM) is employed. Kinematic wave modeling with DQM was applied to a real flood problem for the first time in this study. For this purpose, the flood which occurred in Sütçü ler Degirmendere, a branch of Aksu River, was considered. The DQM simulated the measured hydrograph more suitably than Muskingum Method.
Kinematik Dalga Modelinin Dqm ile Çözümü ve Sütçüler Taşkíní Örneǧi
Keywords: Differential Quadrature Method; Flood Routing; Kinematic Wave; Muskingum Method